IFRS sustainability requires further governance reform - Nicolas Véron (Bruegel, 2009)
This Policy Contribution reproduces the text of a letter sent by Senior Fellow Nicolas Véron to Gerrit Zalm, the Chairman of the International Accounting Standards Committee Foundation (IASCF) in response to the Foundation's public consultation on Part 2 of its Constitution Review. Véron writes that a broader strategic readjustment on the part of the IASCF is necessary if the Foundation hopes to regain the support of the global investment community, its most crucial group of stakeholders. The Foundation must make itself more responsive and accountable to the investment community, a requirement that has become more urgent due to the crisis.
Keywords: 330; International Financial Reporting Standards; EU-Bilanzrecht; EU-Staaten